Unilateral contact and damage analysis in masonry arches - Campo, M.; Drosopoulos, G. A.; Stavroulakis, G. E. (Vietnam Journal of Mechanics, 2009)
In the present work the ultimate failure load and the collapse mechanism of a stone arch bridge are estimated by the usage of (a) a multi - part elastic model with unilateral contact frictional interfaces and (b) a continuous damage model. According to the contact model, contact interfaces simulating potential cracks are considered and their opening or sliding indicates crack initiation. The second model deals with the material damage consisting in the development of internal micro cracks that affect the load bearing capacity of the material. Satisfactory comparison of the results is reported here.